A review of arrangements internationally to accommodate examinees who are bereaved or ill at the time of scheduled second-level school leaving examinations - Murchan, Damian (State Examinations Commission, 2022)
This report describes the findings from a review of how other jurisdictions and education systems address specific issues connected with student access to assessments and certification in the event of serious illness, bereavement or extenuating circumstances connected with the Covid-19 pandemic. The context covers large-scale, high-stakes exit examination settings similar to the Leaving Certificate Examination in Ireland. One issue that has arisen in recent years in relation to the Leaving Certificate is the extent to which the exam processes are sufficiently flexible to cater for the needs of those students who miss or are likely to miss examinations as a result of serious illness or a bereavement close to the time of examinations. A small number of such cases arise annually, and the State Examination Commission (SEC) has been exploring possibilities for addressing these instances in an appropriate manner, with regard to the needs of students who experience such trauma and adversity and being mindful also of the requirement to maintain robust examination and certification procedures and standards. Specific arrangements to address the issue of students impacted by the bereavement of a close family relative were put in place for the 2019 examination on a pilot basis, as part of the existing Reasonable Accommodations at the Certificate Examinations (RACE) process. This initiative gave eligible candidates the option to defer up to three consecutive days of exams from June to a special exam administration in July, to allow the student to attend the funeral of a close relative during the June exam period. While the RACE process also facilitates some limited adjustments to the examination environment and timing for students who experience illness during examinations (SEC, 2021a, 2021b), these adjustments focus on providing special accommodations during the exam (for example taking an exam in a hospital setting) or adjusting the schedule of the exam, on the same day. Other than the pilot arrangements in August 2019, there have traditionally been no alternative options for students whose medical or other circumstances do not allow them to take the exam on the same day as other candidates in the same subject. Considering the concerns above, arrangements to facilitate a supplementary Leaving Certificate Examination in July 2022 for students who are unable to sit the June exams due to close family bereavement, COVID-19 illness and other serious illness have been developed by the SEC. The present review aims to inform discussion about the options for planning and implementing alternative arrangements for students who are unable to present for scheduled exams due to unexpected adversity and trauma. The review provides an analysis of how similar challenges are addressed in other examination systems internationally. The investigation adopted a blended desk-based and empirical methodology, drawing on data gathered from the academic literature, websites and reports associated with ministries of education and examination agencies/awarding bodies, and discussions with key personnel in a number of jurisdictions. The review identifies 19 examination systems sharing reasonable similarity with the Leaving Certificate programme undertaken by Irish post-primary school students and its associated certification. Detailed analysis of information publicly available online explored structural features of assessment and certification systems. This included the purpose and structure of examinations, use of results, timing of assessments, weighting of examinations and coursework if applicable, any policies on alternative arrangements for students unable to sit exams at scheduled times, and the visibility and importance attached to the exams in public discourse. Case study interviews and/or written communication with examination officials in selected systems explored these issues in more detail, especially focusing on procedures and practices underpinning efforts to provide alternative avenues for examination and certification to students who are unable to sit scheduled assessments due to serious illness, bereavement or issues associated with COVID-19. A rapid literature review audited the extent to which issues relating to alternative arrangements for students who miss scheduled high stakes examinations has featured in the academic literature. This report charts the progress of the investigation and provides an overview of findings. It is hoped that the insights gained from the review will be of assistance to the SEC in developing protocols in relation to the Leaving Certificate Examination.
PUBLISHED
Keywords: Inclusive Society; Making Ireland; Assessment of Student Learning; Educational Planning/Policy; Educational Testing/Measurement; Emotional-behavioural Problems; Education; Policy